Developing Lean – EMS Integration Database for Sustaining ISO 14000 Certification - A. P., Puvanasvaran; V. A. , Alagendran; N., Norazlin (Horizon Research Publishing, 2014)
This paper highlights a methodology to implement Lean-EMS integration system in the case study company. Lean manufacturing is a concept widely applied in industries to eliminate wastes and achieve high business efficiency. The concept implemented through five principles which is called a self-sustaining cycle. EMS on the other side is an international standard for environmental management. It guides organizations through compliance requirements to reduce environmental impacts from business activities and boost up operating efficiency. Researches on EMS implementation have revealed that the system has similarity with Lean Principles. Hence, researchers had integrated both systems to attain both lean and EMS goals. This integration required a management system for continuous improvement. This paper focuses on design, and development of database system to manage the integration of Lean Principles and Environmental Management System (EMS) to aid employees in problem solving through visual indicators for continuous improvement and sustain the certification. The methodology adapted for the study is using the database development steps with Microsoft Access 2010 software. The database which is comprised of five performance measures (each reflects a lean principle and selected EMS clause) from integration framework specially designed and developed for the case study company. The results of the study validated the use of developed database system for continuous improvement. The study is indeed very useful to the company because the developed system is a comprehensive tool, where it can visualize problems in operations that might affect the production flow and EMS compliance. As the problem visualized, immediate problem solving can be done to continuously improve the conditions and sustain EMS certification.